Chromosome segment substitution lines: a powerful tool for the Introgression of valuable genes from oryza wild species into cultivated rice (O. sativa) - Liakat Ali, M; Sánchez, P.L.; Yu, S; Lorieux, Mathias; Eizenga, GC (Springer, 2010)
Wild species of rice (genus Oryza) contain many useful genes but a vast majority of these genes remain untapped to date because it is often difficult to transfer these genes into cultivated rice (Oryza sativa L.). Chromosome segment substitution lines (CSSLs) and backcross inbred lines (BILs) are powerful tools for identifying these naturally occurring, favorable alleles in unadapted germplasm. In this paper, we present an overview of the research involving CSSLs and BILs in the introgression of quantitative trait loci (QTLs) associated with the improved performance of rice including resistance to various biotic and abiotic stresses, and even high yield from wild relatives of rice and other unadapted germplasm into the genetic background of adapted rice cultivars. The CSSLs can be used to dissect quantitative traits into the component genetic factors and evaluate gene action as single factors (monogenic loci). CSSLs have the potential to uncover new alleles from the unadapted, non-productive wild rice accessions, develop genome-wide genetic stocks, and clone genes identified in QTL studies for functional genomics research. Recent development of high-density single-nucleotide polymorphism (SNP) arrays in rice and availability of custom-designed medium- and low-density SNP arrays will enhance the CSSL development process with smaller marker-defined segment introgressions from unadapted germplasm.